Analisis Karakteristik Massa Batuan di Sektor Lemajung, Kalan, Kalimantan Barat - Syaeful, Heri; Kamajati, Dhatu (BRIN Publishing, 2015)
Rock mass characterization is required in design of rock opening, which calculation of engineering characters of rock mass become one important parameter toconsider. Lemajung sector is one of prospect area for uranium mining in Kalan, West Kalimantan. Purpose of research is to acquire rock mass characteristicsas basic data for planning the development of mining technique of ore deposit. Methodology applied is rock sampling for rock mechanic laboratory analysis, observation of joints, and observation of groundwater condition. Rock parameters analyzed includes uniaxial compressive strength (UCS), rock quality designation (RQD), joint spacing, joint condition, and groundwater. Analysis concluded that metasiltstonewhich is lithology contained uranium in Lemajung Sector has rock mass rating (RMR) value of 56 or rock mass class III: fair rock in the depth of around 60 m, and in the depth of 280 m RMR value reach 82 or rock mass class I: very good rock. RMR value data furthermore could be used for analysis of tunneling in the model of underground mine or slope stability analysis in the model of open pit mine.